THE ROLE OF ROBOTICS AND AUTOMATION IN INDUSTRY 4.0 TRANSFORMATION - Loso Judijanto (Information Technology Studies Journal (ITECH), 2025)
Industry 4.0 transformation has driven the adoption of robotics and automation, but challenges in implementation are still a significant obstacle for many companies. This research aims to identify and analyze the main challenges faced in the application of robotics technology in the industrial sector. This study focuses on grouping technical, economic, regulatory, social and security challenges that hinder the adoption of robotics in the context of industry 4.0. This research uses a Systematic Literature Review (SLR) approach to collect and analyze data from relevant scientific articles, with strict inclusion and exclusion criteria. Analysis was carried out using the PRISMA framework to ensure transparency and validity of the results. Research findings show that the main challenges in robotics implementation include system interoperability, high implementation costs, regulatory uncertainty, social resistance to automation, and cybersecurity risks. The impact of these challenges can hinder innovation and efficiency in the industry. The results of this research provide important insights for practitioners and policy makers to design effective mitigation strategies in facing the challenges of robotics adoption. In addition, this research also contributes to the development of technology adoption theory in industry 4.0 by providing an evidence-based analysis of the obstacles faced.